2005
DOI: 10.1095/biolreprod.104.029520
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium: An Endocrine Disrupter That Affects Gene Expression in the Liver and Brain of Juvenile Rainbow Trout1

Abstract: An inhibition of vitellogenesis is observed in fish exposed to cadmium (Cd), either in natural or in experimental conditions. To investigate whether this correlates or not with modifications in the expression of several genes involved in reproduction, we have performed a study on juvenile rainbow trout (Oncorhynchus mykiss) exposed to waterborne Cd in combination with estradiol (E2). A relative reverse transcription-PCR protocol was used to evaluate the effect of Cd exposure on the expression of several genes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 45 publications
4
35
0
Order By: Relevance
“…The particular sensitivity of the testis to cadmium exposure may be related to the testis being a highly proliferative and acutely hormone-dependent organ. Recent evidence concerning the direct and indirect impairment, at low cadmium doses, of steroidogenic activities, with the subsequent induction of germ cell apoptosis (Ozawa et al 2002;Gupta et al 2004) are consistent with its endocrine disruptive actions in other tissues (Choe et al 2003;Vetillard and Bailhache 2005).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The particular sensitivity of the testis to cadmium exposure may be related to the testis being a highly proliferative and acutely hormone-dependent organ. Recent evidence concerning the direct and indirect impairment, at low cadmium doses, of steroidogenic activities, with the subsequent induction of germ cell apoptosis (Ozawa et al 2002;Gupta et al 2004) are consistent with its endocrine disruptive actions in other tissues (Choe et al 2003;Vetillard and Bailhache 2005).…”
Section: Introductionmentioning
confidence: 68%
“…Nuclear-associated cadmium may displace zinc in polymerases, other metalloenzymes or transcription factors, all of which are present in larger amounts in the nuclei of proliferating cells (Din and Frazier 1985) or it may directly induce chromatin changes (Banfalvi et al 2005). Interestingly, classic androgen and oestrogen receptors, both zinc-finger proteins, are concentrated in PrM regions of the shark testis (Callard et al 1985;Cuevas and Callard 1992) and cadmium can reduce liver vitellogenin expression through its direct binding to oestrogen receptor-α in the trout (Vetillard and Bailhache 2005). Furthermore, since the Sertoli cell is the sole steroid-producing element in Squalus (Pudney and Callard 1984), cadmium-induced inhibition of steroidogenic activities in mid-stage PrM cysts might result in their increased apoptotic death, as is known for the rat (Ozawa et al 2002;Gupta et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, if exogenous estrogens are present, the response elicited by metals could be modified. Vetillard and Bailhache (2005) showed that E 2 treatments did not modify GnRH1and GnRH2 mRNA levels in the brain of rainbow trout. However, Cd in combination with E 2 stimulated these mRNAs.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, some metals could disrupt the GnRH-gonadotropins system by alteration of calcium homeostasis (Yuan et al 2013). In the brain of rainbow trout (Oncorhynchus mykiss) exposed to Cd (5 and 10 μg/L) mRNA levels of GnRH1and GnRH2 was greatly enhanced in a concentration-dependant manner; probably because Cd alters E 2 signalling pathways and could affect the reproductive axis by non-estrogenic mechanisms (Vetillard and Bailhache 2005). However, if exogenous estrogens are present, the response elicited by metals could be modified.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cadmium has recently become the subject of many investigations (16,(21)(22)(23)(24)(25). The toxic effects of cadmium investigated in freshwater fish include development abnormalities detected in many teleost species (26)(27)(28). Cadmium led to larval teratogenic and developmental abnormalities (29), to micronucleus induction at environmental levels of 2, 10, and 30 µg L -1 , and to increased concentration-dependent quantities of micronucleus after contamination with 10 and 30 µg L -1 in Xenopus larvae (30).…”
mentioning
confidence: 99%